Development of Technical Drawing Learning Modules as Teaching Materials for Technical Drawing Subjects in Class X of the BKP Department at SMK Negeri 1 Botomuzoi for the 2022/2023 Academic Year - Lahagu, Maretinus; Zebua, Yelisman (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to create a Technical Drawing learning module suitable for use in the Technical Drawing subject at SMK Negeri 1 Botomuzoi, adhering to predefined criteria. Additionally, the research aims to evaluate the suitability of the created Technical Drawing learning module as a teaching aid in the Technical Drawing subject for Class X students in the BKP Department at SMK Negeri 1 Botomuzoi. The research employs the Borg & Gall development model, simplified by Anik Ghufron, as a Research and Development (R&D) approach. The development procedure consists of four stages: preliminary study, development, field testing, and dissemination. The outcome of this research is a Technical Drawing Learning Module deemed suitable for use as a learning resource in Class X of the BKP Department at SMK Negeri 1 Botomuzoi. Overall, the average evaluations by subject matter experts, media experts, and student feedback indicate positive outcomes.